2015
DOI: 10.1039/c5py01091h
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-acryloyl ciprofloxacin-co-acrylic acid) grafted magnetite nanoparticles for microbial decontamination of collagen solution: have we conquered the problem of antimicrobial residues?

Abstract: Widespread concern over antimicrobial toxicity and resistance development necessitates the thorough recovery of antimicrobial compounds from decontaminated collagen. Herein, ciprofloxacin molecules were acryloylated by reaction of the secondary amine in 7-piperazinyl substituent with acryloyl chloride, and then covalently immobilized, for the first time, on the vinyl-functionalized Fe 3 O 4 nanoparticle surface via graft copolymerization with acrylic acid, in an effort to design a magnetically-recoverable nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…After that, the precipitate was dried, redissolved in anhydrous DCM, and refined by silica gel chromatography (DCM-methanol 2%) to obtain the final product (1.38 g, 78% yield). Chemical structure of the product was confirmed by FT-IR, 1 H and 13 C NMR spectroscopies, which could be found in our previous publications. , …”
Section: Experimental Sectionsupporting
confidence: 76%
See 2 more Smart Citations
“…After that, the precipitate was dried, redissolved in anhydrous DCM, and refined by silica gel chromatography (DCM-methanol 2%) to obtain the final product (1.38 g, 78% yield). Chemical structure of the product was confirmed by FT-IR, 1 H and 13 C NMR spectroscopies, which could be found in our previous publications. , …”
Section: Experimental Sectionsupporting
confidence: 76%
“…To this end, ciprofloxacin was acryloylated by site-specific reaction of the secondary amine in the 7-piperazinyl substitute with acryloyl chloride. Our recent investigations , showed that the resultant N -acryloyl ciprofloxacin was still bioactive, because the 3-carboxyl, 4-keto, and quinolone pharmacophore, all essential for hydrogen-bonding with DNA gyrase and topoisomerase IV to elicit inhibitory action on in vivo DNA synthesis, remained intact. By consecutive RAFT polymerization, the PNIPAM “tail” was attached to the antibiotic “head” via noncleavable linkages, preventing artifacts by undesirable release of small-molecule antibiotics.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, the DOX-CNC spectra contain a peak at 400 eV raised from the nitrogen atom of DOX, while the spectrum for CIP-PCNC shows peaks at the binding energy of 687.7 and 400 eV, which are related to the fluorine and nitrogen of CIP on the PCNC (Figure S4). Elevated peaks at 164.2 and 400 eV in the SMX-PCNC spectrum are also ascribed to sulfur and nitrogen contents of SMX, revealing its adsorption on PCNC.…”
Section: Resultsmentioning
confidence: 96%
“…The CD spectrum of unordered collagen is usually characterized by a single band below 200 nm, whereas triple-helical structure usually presents one negative band at 223 nm, along with one positive band at 197 nm. 19,20 It has been well established that the absolute ratio value of molar ellipticity at 220 nm over molar ellipticity around 195-197 nm (Rpn) can be used to characterize the integrity of triple-helical conformation of collagen in solution. As shown in Fig.…”
mentioning
confidence: 99%